Durability of adhesive glass-metal connections for structural applications. (1st November 2016) - Van Lancker, Bert; Dispersyn, Jonas; De Corte, Wouter; Belis, Jan
Highlights: Adhesive point-fixings and linear adhesive glass-metal connections are investigated. A new artificial ageing schedule is developed based on available technical standards. Effects of moisture, thermal cycling and UV-radiation are studied during experiments. Moisture is the most severe ageing condition for the examined MS-polymer and epoxy. The studied structural silicone is very well suited for high-demanding applications. Abstract: The use of adhesive bonds for structural glass-metal connections in the building envelope has increased in recent years. Despite the multiple advantages compared to more traditional bolted connections, long-term behaviour and durability of the adhesives have to be investigated accurately. Because, under service conditions, these products are exposed to factors, such as moisture, temperature and UV-radiation, which may influence their performance significantly. Sufficient data on the durability of adhesive glass-metal connections subjected to environmental factors is therefore essential, however, not always available. In an attempt to partially fill this gap, experimental tests were performed on three potential adhesives for structural glass-metal connections. During previous research, a stiff epoxy, 3M™ Scotch-Weld™ 9323 B/A, and a flexible MS-polymer, Soudaseal 270 HS, were selected for point-fixings, and a structural silicone, Sikasil® SG-500, for linear connections between glass and cold-formed steel. This paper reports on the effects of moisture, temperature and UV-radiation on the mechanical properties of structural point-fixings and linear glass-metal connections. According to the tests, both the epoxy and MS-polymer demonstrated limited resistance against moisture, while the performance of the silicone after exposure to moisture was outstanding. Thermal cycling did not significantly affect the 3M™ Scotch-Weld™ 9323 B/A and the Sikasil® SG-500. For the Soudaseal 270 HS, thermal cycling improved the mechanical properties. The exposure to UV-radiation had no effect on the MS-polymer and silicone, but did aggravate previous damage caused by moisture in case of the epoxy. Overall, it was concluded that the epoxy, 3M™ Scotch-Weld™ 9323 B/A, and the MS-polymer, Soudaseal 270 HS, are possible candidate adhesives from a durability point of view for point-fixings in façades as moisture can be easily controlled for this application. The structural silicone, Sikasil® SG-500, seems ideal for both indoor and outdoor applications. Moreover, its excellent adhesion to galvanised cold-formed steel under severe environmental conditions might give rise to the development of new structural concepts.